2010
DOI: 10.1186/1471-2458-10-525
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early psychosocial factors (childhood socioeconomic factors and adversities) on future risk of type 2 diabetes, metabolic disturbances and obesity: a systematic review

Abstract: BackgroundPsychological factors and socioeconomic status (SES) have a notable impact on health disparities, including type 2 diabetes risk. However, the link between childhood psychosocial factors, such as childhood adversities or parental SES, and metabolic disturbances is less well established. In addition, the lifetime perspective including adult socioeconomic factors remains of further interest.We carried out a systematic review with the main question if there is evidence in population- or community-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(105 citation statements)
references
References 88 publications
(164 reference statements)
5
96
0
4
Order By: Relevance
“…On the other hand, it should be added that children following traditional dietary pattern in this study were older and had older maternal age, larger family, and lower parental education. These factors are all risk factors for overweightness and obesity in children (34)(35)(36). This positive relationship between traditional dietary pattern and increased body mass index and obesity among adults was also observed in a study by Falahi et al (37).…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, it should be added that children following traditional dietary pattern in this study were older and had older maternal age, larger family, and lower parental education. These factors are all risk factors for overweightness and obesity in children (34)(35)(36). This positive relationship between traditional dietary pattern and increased body mass index and obesity among adults was also observed in a study by Falahi et al (37).…”
Section: Discussionsupporting
confidence: 69%
“…The impact of psychosocial factors, such as deprivation, trauma, and neglect has been considered, but more studies are needed to draw conclusions regarding impact on obesity [44]. Factors including stress, income, sleep, and racism have been associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, epidemiologic studies in individuals with a history of pediatric stress exposure have shown a higher risk for developing a psychiatric disorder (anxiety, depression, and posttraumatic stress disorder [PTSD]) [5-7]. In addition, early-life stress has been associated with a higher prevalence of cardiometabolic diseases and chronic inflammatory and pain syndromes [8-10]. The strong relations between pediatric stress and adverse mental and physical health outcomes in adult life have generated considerable interest in investigating the underlying pathophysiologic and neurobiologic mechanisms that link these conditions (Fig.…”
Section: Introductionmentioning
confidence: 99%